CYTOKINE AND OXIDATIVE STRESS PROFILES IN CERVICOVAGINAL MUCUS OF COWS AT INSEMINATION: ASSOCIATIONS WITH PREGNANCY AND CALF SEX - Kilinc, M. A.; Risvanli, A. (Pakistan Agricultural Scientists Forum, 2025)
This study aimed to examine the relationship between the Th1/Th2 cytokine balance and oxidative stress parameters in the cervicovaginal mucus of cows at the time of insemination. It also investigated the potential associations of these factors with conception rates and calf sex. Cervicovaginal mucus samples were collected from 90 cows at the time of insemination. Of these, 55 cows were confirmed pregnant (Group I), and 33 were non-pregnant (Group II). Ultimately, 35 female and 20 male calves were born. The mucus samples were analyzed for interleukins (IL) -2, IL -4, IL -5, IL -10, tumor necrosis factor-alpha (TNF alpha), interferon-gamma (IFN-gamma), and oxidative stress markers including malondialdehyde (MDA), glutathione (GSH), glutathione peroxidase (GSH-Px), catalase (CAT) and superoxide dismutase (SOD). IFN-gamma levels were higher in pregnant cows, while MDA levels were higher in non-pregnant cows. Among parturient cows, those that gave birth to male calves had higher levels of IL-2 and GSH compared to those with female calves. Based on these findings, cytokine and oxidative stress parameters in cervicovaginal mucus may not serve as reliable biomarkers for predicting pregnancy success or calf sex. Furthermore, no significant differences in Th1/Th2 cytokine balance were observed in relation to pregnancy status or offspring gender.
Keywords: Cow; cervicovaginal mucus; cytokine; oxidative stress